Accountability of village fund management during the covid-19 pandemic (Study on village government in Dayun District, Siak Regency) - Sahala Purba; Junika Napitupulu; Andro Siregar (Universitas Hayam Wuruk Perbanas, 2023)
This study aims to examine the effect of the competence of village government officials, citizen participation, application of information technology, organizational commitment, transparency, and internal control systems on the accountability of village fund management in village government. This study is a quantitative study using primary data obtained by distributing questionnaires. The analysis method used is multiple linear regression. This study was conducted in 11 villages in Dayun District, Siak Regency, Riau Province, Indonesia.Â Each village was represented by 4 respondents consisting of the village head, village secretary, financial officer, and 1 member of the Village Consultative Agency (BPD). The research was conducted from April to May 2022. The results show that the competence of village officials, citizen participation, the application of information technology, and internal control systems have an effect on the accountability of village fund management, but organizational commitment and transparency have no effect on the accountability of village fund management. Adequate competence of village officials, high citizen participation, application of good information technology, and application of an appropriate internal control system can increase the accountability of village fund management during the COVID-19 pandemic.